Public health messages about antibiotic treatment for respiratory tract infection may increase perceived symptom severity reporting - Lawrence, Claire; Eamonn, Ferguson (SAGE, 2016)
Public health campaigns to reduce expectations for antibiotic treatment for respiratory tract infections (RTIs) have shown little or no effect on antibiotic prescribing and consumption. We examined whether such messages can increase RTI symptom reporting. Participants (N = 318) received one of four campaign messages, a combination of all four messages or no message. RTI symptoms increased for those who received information emphasizing the ineffectiveness of antibiotic treatment for RTIs. As symptom severity is associated with greater contact with primary healthcare and receiving antibiotic prescriptions, campaigns to encourage antimicrobial stewardship should consider the side effects of antibiotic ineffectiveness messages.